8=x-square(x-6)

Simple and best practice solution for 8=x-square(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8=x-square(x-6) equation:


Simplifying
8 = x + -1square(x + -6)

Reorder the terms:
8 = x + -1aeqrsu(-6 + x)
8 = x + (-6 * -1aeqrsu + x * -1aeqrsu)
8 = x + (6aeqrsu + -1aeqrsux)

Reorder the terms:
8 = 6aeqrsu + -1aeqrsux + x

Solving
8 = 6aeqrsu + -1aeqrsux + x

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6aeqrsu' to each side of the equation.
8 + -6aeqrsu = 6aeqrsu + -1aeqrsux + -6aeqrsu + x

Reorder the terms:
8 + -6aeqrsu = 6aeqrsu + -6aeqrsu + -1aeqrsux + x

Combine like terms: 6aeqrsu + -6aeqrsu = 0
8 + -6aeqrsu = 0 + -1aeqrsux + x
8 + -6aeqrsu = -1aeqrsux + x

Add 'aeqrsux' to each side of the equation.
8 + -6aeqrsu + aeqrsux = -1aeqrsux + aeqrsux + x

Combine like terms: -1aeqrsux + aeqrsux = 0
8 + -6aeqrsu + aeqrsux = 0 + x
8 + -6aeqrsu + aeqrsux = x

Add '-8' to each side of the equation.
8 + -6aeqrsu + -8 + aeqrsux = -8 + x

Reorder the terms:
8 + -8 + -6aeqrsu + aeqrsux = -8 + x

Combine like terms: 8 + -8 = 0
0 + -6aeqrsu + aeqrsux = -8 + x
-6aeqrsu + aeqrsux = -8 + x

Reorder the terms:
8 + -6aeqrsu + aeqrsux + -1x = -8 + x + 8 + -1x

Reorder the terms:
8 + -6aeqrsu + aeqrsux + -1x = -8 + 8 + x + -1x

Combine like terms: -8 + 8 = 0
8 + -6aeqrsu + aeqrsux + -1x = 0 + x + -1x
8 + -6aeqrsu + aeqrsux + -1x = x + -1x

Combine like terms: x + -1x = 0
8 + -6aeqrsu + aeqrsux + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| ab+3b= | | 14-2m=26 | | 6x-3=6(x+9) | | 3q-11=61-3q | | 2y-12+3y=6+5y | | 3x+4=-8-5x | | 3x+8-2x=9+4x-7 | | 2+3.5(z+2)=5.5z-5 | | 8(x+2)+6(x+2)=7x-7 | | 6(z^2+1)=-13z | | x(5x+17)=2x^2-5x+16 | | 1+109x+45x-1=154 | | 9m^2+144=78m | | 4(x+8)=x+5 | | 0.55x+0.3x=x-10.5 | | 4(3x-2y)=(3y-2x) | | (3x-9)(x^2-4x-x+4)+(2x-4)(x^2-4x-x+4)=(4x-12)(x^2-4x-2x+8)+(x-3)(x^2-x-2x+2) | | 12-k-2=6k-11 | | 8x^3-4x^2+7x-1=0 | | 0.4x+3.6=0.3x+1.3 | | (3x-4)+(2x+1)= | | 8(x+2)=7x-7 | | 1.35p=40.5 | | -4+x=6+x | | 3n=14-4 | | 27=x+1+(2x+1)+5x | | 14-(5m+8)=2+3m-12 | | 9x+7y=-9 | | 9x+(-2x)= | | 3n+6=3 | | y=2x^2+9x+7 | | r(x)=10x-.002x^2 |

Equations solver categories